2010
DOI: 10.1185/03007995.2010.525489
|View full text |Cite
|
Sign up to set email alerts
|

Second-line therapy for NSCLC in clinical practice: baseline results of the European SELECTTION observational study

Abstract: In this observational study, pemetrexed, then docetaxel and erlotinib were the most frequently prescribed second-line treatments, which is in line with international guidelines. Erlotinib was most commonly prescribed to that subset of patients expected to gain the greatest benefit (those with adenocarcinoma, never-smokers and females). Pemetrexed was more frequently prescribed than docetaxel, with physicians most commonly choosing to prescribe the former agent because of its tolerability profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Median OS estimates were close to 8 months in 2 studies that reported this information specifically for patients with adenocarcinoma in the second-line setting [18, 22, 27]. Median OS estimates were reported from the time of third-line treatment initiation in 4 studies and median OS ranged from 3.8 (95% CI, 2.6–5.4) to 12.0 months (95% CI, 9.3–14.2) [13, 24, 25]…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Median OS estimates were close to 8 months in 2 studies that reported this information specifically for patients with adenocarcinoma in the second-line setting [18, 22, 27]. Median OS estimates were reported from the time of third-line treatment initiation in 4 studies and median OS ranged from 3.8 (95% CI, 2.6–5.4) to 12.0 months (95% CI, 9.3–14.2) [13, 24, 25]…”
Section: Resultsmentioning
confidence: 98%
“…The proportion of patients who never smoked was highest in the Japanese cohort [13,]. Five studies reported performance status after first-line therapy or at initiation of second-line therapy, with most patients having a Karnofsky Performance Status of 70 or better or an Eastern Cooperative Oncology Group score of 0 or 1 [15, 16, 18, 21, 24, 27]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pemetrexed is now the preferred second-line treatment for NSCLC in the USA 24. In recent years, clinical researchers had demonstrated the positive effects of this agent in advanced NSCLC, and pemetrexed has gradually become a first-line agent for treatment of the disease 23.…”
Section: Discussionmentioning
confidence: 99%